Synthesis, Self-assembly, and in vitro Biocompatibility of a Novel Steroidal Oxime - Chou, Tzung-Han; Chen, Chien-Wen (Current Pharmaceutical Biotechnology, 2015)
A novel steroidal oxime (SO) was synthesized using an economic method and then characterized by Fourier transform infrared (FTIR) and 1H nuclear magnetic resonance (NMR). When dispersed in pure water, SO can self-assemble into a nano-scale circular structure which was verified by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The formation of SO nano aggregates may result from its ambiphilic characteristic which has the hydrophobic cholesterolbased backbone and the hydrophilic oxime head group. The prepared SO aggregates were then examined for its in vitro biocompatibility using the human keratinocytes cell line (HaCaT) as a representative skin exposure model. The biocompatibility was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and cell morphology observation. The results showed that the nano-scale SO aggregates did not cause serious damage to HaCaT cells at the designed concentrations and suggested that SO could be a potential material for preparing cosmeceutical carrier.
Keywords: synthesis